Erato : journal of the International Lesbian and Gay Cultural Network. (Berlin : ILGCN e.V., 1993)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie: Pf 150, 10412 Berlin
Engels
Periodiek